Ginger family from Bueng Kan Province, Thailand: Diversity, conservation status, and traditional uses - AREERAT RAGSASILP; PIYAPORN SAENSOUK; SURAPON SAENSOUK (Society for Indonesian Biodiversity, 2022)
Abstract. Ragsasilp A, Saensouk P, Saensouk S. 2022. Ginger family from Bueng Kan Province, Thailand: Diversity, conservation status, and traditional uses. Biodiversitas 23: 2739-2753. The objective of this study was to determine the diversity, conservation status, and traditional uses of Zingiberaceae in Bueng Kan Province, Thailand. The family Zingiberaceae was collected during field surveys in Bueng Kan Province, northeastern Thailand between January and December 2021. Three tribes, 13 genera, and 67 species of Zingiberaceae were found. The genera with the highest diversity were Curcuma (12 species), Zingiber (11 species), Globba (10 species), Alpinia (eight species), Kaempferia (seven species), Amomum (six species), Caulokaempferia (four species), Boesenbergia (three species), Gagnepainia (two species), Etlingera (one species), Hedychium (one species), Meistera (one species) and Wurfbainia (one species). Bung Khla district was found to have the most diverse species in this family with 64 species. The family was discovered in five ecosystem types, deciduous dipterocarp forest (20 species), mixed deciduous forest (21 species), dry evergreen forest (20 species), river basin (two species), and cultivated in home gardens (24 species). There were 41 native species found (62.68%), while 16 species (23.88%) were recognized as being cultivated in home gardens. The highest phenology rate was recorded from March to September. Thirty-eight species were reported to have the conservation status as rare species. Twenty-eight species were recognized as common species. Nine species, namely Alpinia macrostaminodia, Amomum biphyllum, A. wandokthong, Globba laeta, Boesenbergia baimaii, Caulokaempferia jirawongsei, Ca. Phutonkensis, Ca. phuwoaensis and Ca. phulangkaensis were recorded as endemic species to Thailand. Moreover, A. macrostaminodia, A. biphyllum, A. monophyllum, C. jirawongsei, Ca. phutokensis, Ca. phuwoaensis and Curcuma pygmaea, were found only in Bueng Kan Province, Thailand. This study reported nine species to be rare plants in Bueng Kan Province. Twenty-nine species of the family Zingiberaceae from Bueng Kan Province were presented in IUCN (2022): CR (1 species), DD (9 species), EN (2 species) LC (16 species), NT (1 species). The Zingiberaceae in Bueng Kan Province had popular uses as food, spice, rituals, and ornamentals. For the medicinal use of Zingiberaceae in this study, they were in relation to flatulence, laxative, diuretic, stomachache, treatment of inguinal hernia, uterine involution, antipruritic, cosmetic, skin disease, carminative, antiflatulent, intoxication, and tonic. In Thailand, 42 species of Zingiberaceae are reported for the first time to have traditional uses. Therefore, the information on the diversity, conservation status, and traditional uses are important as biological resources of the Zingiberaceae in Bueng Kan Province, Thailand.